Health and well-being: art therapy for health professionals working in outpatient care settings - Oneide Regina Depret; Edmara Bazoni Soares Maia; Regina Issuzu Hirooka de Borba; Circéa Amália Ribeiro (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objectives: To enable health professionals, in an outpatient care setting, to experience the group process of art therapy and to understand the meaning given by him/her to this experience. Method: A qualitative study, using Symbolic Interactionism and Qualitative Conventional Content Analysis as theoretical and methodological frameworks, respectively. Eight health professionals working in the outpatient clinic of a philanthropic institution participated in the art therapy process and later in semi-structured interviews. Results: For the professionals, art therapeutic workshop was an amazing and rewarding experience, a space of interaction that allowed them to know each other better, to respect and learn from their colleagues, to relax, relieve stress and express their emotions. It was defined as a therapeutic experience, promoter of health and well-being, prompting professionals to want the workshops to continue. Conclusions and implications for practice: The study contributes to the reflection and discussion about workers' health and to the need to create therapeutic resources, such as art therapy, as a support tool for their mental health and well-being. Innovative and creative interventions must be incorporated into health services to address the global clamor, emphasizing the need to promote mental health, especially for health professionals, which calls for urgent measures.